2015
DOI: 10.1042/bst20150060
|View full text |Cite
|
Sign up to set email alerts
|

Frequency modulated translocational oscillations of Nrf2, a transcription factor functioning like a wireless sensor

Abstract: The discovery that nuclear factor erythroid 2-related factor 2 (Nrf2) undergoes translocational oscillations from cytoplasm to nucleus in human cells with frequency modulation linked to activation of a stress-stimulated cytoprotective response raises the prospect that the Nrf2 works mechanistically analogous to a wireless sensor. Herein, we consider how this new model of Nrf2 oscillation resolves previous inexplicable experimental findings on Nrf2 regulation and why it is fit-for-purpose. Further investigation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 38 publications
(48 reference statements)
0
16
0
Order By: Relevance
“…Herein we found that tRES also induces expression of Glo1 with high E max . Our recent studies (7,8) and those of others (31) suggest that this is achieved by preventing nuclear acetylation and inactivation of Nrf2 via increasing in situ activity of sirtuin-1. At low tRES concentrations, this occurs through inhibition of cAMP phosphodiesterases, activation of AMPK, and increased NAD + .…”
Section: (232%) [-]mentioning
confidence: 99%
See 4 more Smart Citations
“…Herein we found that tRES also induces expression of Glo1 with high E max . Our recent studies (7,8) and those of others (31) suggest that this is achieved by preventing nuclear acetylation and inactivation of Nrf2 via increasing in situ activity of sirtuin-1. At low tRES concentrations, this occurs through inhibition of cAMP phosphodiesterases, activation of AMPK, and increased NAD + .…”
Section: (232%) [-]mentioning
confidence: 99%
“…Activation of Nrf2 by dietary bioactive compounds is mostly studied through ARE-linked induction of NQO1 or HMOX1 expression. Small-molecule activators of Nrf2 increase expression of different ARE-linked gene subsets (6,7)-likely due to the ability of Nrf2 activators to recruit the requisite accessory proteins and increase nuclear concentration of functionally active Nrf2 to the level required for increased expression of the ARE-linked gene of interest (7,8). A specific functional screen for GLO1-ARE transcriptional activation was therefore required.…”
Section: (232%) [-]mentioning
confidence: 99%
See 3 more Smart Citations